The Lecturer's Guide to Quality and Standards in Colleges and Universities - Ashkroft, Kate (Taylor & Francis, 1995)
A follow-up volume to "Managing Teaching and Learning in Further Education and Higher Education", this text provides a guide to managing quality and standards from the lecturer's point of view. It covers key issues such as teaching, learning, student support, assessment, evaluation, course design, bidding for and managing resources, marketing and research.; Based on the model of lecturer as reflective practitioner, this book is intended to help enable the lecturer to make sense of the changing climate of quality control and academic standards. Its interactive design introduces stimulating ideas and suggestions for further reading and provides guidelines on issues of relevance to individual readers.